A Preliminary Analysis of Compassion Satisfaction and Compassion Fatigue With Considerations for Nursing Unit Specialization and Demographic Factors. Issue 3 (May 2017) - Mooney, Claire; Fetter, Katrina; Gross, Brian W.; Rinehart, Cole; Lynch, Caitlin; Rogers, Frederick B.
Abstract : Compassion fatigue (CF), or vicarious traumatization, is a state of physical/emotional distress that results from caring for those experiencing pain. We sought to characterize levels of CF in intensive care unit (ICU) and oncology nursing populations with subanalyses comparing specific personal/professional demographic factors. The Professional Quality of Life (ProQOL) scale, a validated tool for assessing CF, burnout (BO), and compassion satisfaction (CS), was distributed to the ICU and oncology divisions of a community hospital. Demographic data and ProQOL scale scores were collected and compared within specialty and gender subgroups. Two-sample t tests and regression analyses were used to compare groups. Statistical significance was defined as p < .05. A total of 86 nurses submitted completed surveys able to be analyzed. Levels of CS were significantly lower ( p = .023) and levels of BO were significantly higher ( p = .029) in ICU nurses than in oncology nurses. Male nurses exhibited significantly higher CS ( p = .001) and significantly lower BO ( p = .021) and CF ( p = .014) than female nurses. Intensive care unit nurses and female nurses from both ICU and oncology specialties may be at increased risk for developing a poorer overall ProQOL and CF.